Development and protective efficacy of multi-epitope vaccine FL46 against cystic echinococcosis - Jiang, Tingting; Mahemuti, Maerdan; Wang, Weina; Han, Shuai; Wu, Xiaoying; Liu, Hua; Chen, Quan; Mo, Xiaojin; Wang, Xu; Kadiaili, Aerxin; Hu, Yuan; Cao, Jianping; et al. (Frontiers in Immunology, 2025)
Echinococcosis is an important zoonotic parasitic disease caused by Echinococcus spp. Infection. Vaccines represent the most economical and effective means of preventing and controlling echinococcosis. This study aimed to construct a multi-epitope vaccine targeting E. granulosus and evaluate its immunogenicity and protective efficacy against cystic echinococcosis. We identified HLA-bound T-cell epitopes (P1, P2, P3) from the liver of echinococcosis patients using co-immunoprecipitation and incorporated them into the multi-epitope vaccine FL46. In vitro cytotoxicity assessment using BMDCs and U937 cells confirmed that FL46 concentrations below 500 µg/mL did not impair cell proliferation. Forty C57BL/6 mice were randomly divided into vaccine or control groups. The vaccine group received three subcutaneous immunizations (100 µg FL46/mouse, emulsified 1:1 with Freund’s adjuvant) at two-week intervals. Two weeks post-final immunization, all mice were challenged intraperitoneally with 2000 protoscoleces and sacrificed eight months post-infection. Vaccinated mice exhibited significantly elevated serum levels of IL-2, TNF-α, IL-5, IL-6, and Keratinocyte-derived cytokine (KC) after immunization three times. Splenic B1 and B2 lymphocyte proportions increased dramatically eight months after the third immunization. Significantly higher levels of IgM, IgG, and IgG2a were detected in the vaccine group eight weeks post-infection, persisting for at least eight months. The vaccine group demonstrated a significantly reduced cyst burden (number and weight) compared to the controls, corresponding to a 59.16% cyst suppression rate. The indicators of liver fibrosis were also significantly lower in vaccinated mice. These results demonstrate that the multi-epitope vaccine FL46 elicits a robust mixed Th1/Th2 immune response and confers significant protection against cystic echinococcosis, highlighting its potential as a candidate vaccine.